Tarsal Coalition in Children and Adolescent and Recurrent Sprain Frequency - Amel Djerbal; Youssria Akloul-Hamdaoui; SamirTebani; Nazim Sifi (International Journal of Allied Medical Sciences and Clinical Research, 2024)
Tarsal coalitions correspond to an abnormal fusion of one or more tarsal bones. Tarsal coalitions cause pain, stiffness, recurrent sprains, and contracted valgus flat feet in children and adolescents, detrimental to the functional prognosis. They can be difficult to diagnose on standard x-rays, so it is vital to be aware of the indirect radiological signs that may be suggestive. When in doubt, cross-sectional imaging techniques should be used. Despite the fact that it can cause radiation, CTscan is still the gold standard, providing a three-dimensional approach to the bone bridge and allowing comparative bilateral studies. We report the case of a 12-year-old boy with unilateral talo-calcaneal left-wing coalition, who presented with pain, a notion of repeated sprains, stiffness of the back foot with a significant limitation of daily activities and sports.